Influence of Sports Value on Adolescent Participation and Preference of Sci-Tech Experience Activities - Shuang Chen; Zhe Zhou; Kexin Ren (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
Through the combination of sports and education, sci-tech sports enable adolescents to master professional knowledge of sci-tech sports, while building a strong physique. Sports value has a great influence over adolescent participation and preference of sci-tech sports experience activities. However, few domestic scholars have surveyed adolescent preference of sci-tech sports experience activities, or their sports value. Therefore, this paper decides to study how sports value influences adolescent participation and preference of sci-tech sports experience activities. Firstly, the adolescent sci-tech experience was defined under the influence of sports value. Next, the authors judged the emotional state of text reviews on adolescent sci-tech experience, provided the method to compute the emotional score of each text, and explained how to analyze adolescent preference of sci-tech experience activities under the influence of sports value. On this basis, the themed portraits of adolescent sci-tech experience were extracted from different angles, and the effects of time and changing sports value on adolescent preference were evaluated. The proposed algorithm and model were proved effective through experiments.